Analysis of Groundwater Salinity Levels in the Lampulo Coastal Area Kuta Alam Sub-District - Mice Putri Afriyani; Salsabila Salsabila; Muttakin Muttakin; Cut Vita Rajiatul Jummi; Husna Diah (JURNAL GEOGRAFI, 2024)
The problem of seawater seepage in coastal areas can result in a decrease in groundwater quality due to the mixing of seawater and groundwater, so seawater seepage has an impact on increasing salinity, including in the research area. The research location is in the Lampulo beach area, Kuta Alam sub-district. Phreatic well water is generally not liked by residents of this coastal area because it tastes brackish. The high salinity of phreatic groundwater is caused by seawater seepage into alluvial land. The aim of this research is to analyze the level of groundwater salinity in the Lampulo coastal area, Kuta Alam sub-district. This research uses a grid sampling method and criteria for assessing groundwater salinity (o/oo) based on salt content. Groundwater salinity was measured randomly in 50 phreatic wells using a refractometer and marked with sample coordinates using the Avenza Maps application. Field measurement results show that there are variations in salinity values ranging from 0 to 32 ppt. Phreatic well water at the research location based on its salt content is grouped into three groups, namely fresh water, brackish water and salt water. For the freshwater group, a percentage value was obtained with a prevalence of 68%; for the brackish water group, a percentage value was obtained with a prevalence of 26%; and for the salt water group, a percentage value was obtained with a prevalence of 6%.Keywords: Salinity, Groundwater, Phreatic Well, Seawater Seepage, Grid Sampling